Uma leitura do “dharma de arjuna” a partir de elementos da psicologia analítica de Jung - Campo, Adriano Rosatti (2022)
In this dissertation, we propose to develop a reading of the “Bhagavad Gita”, a classic text of Hinduism, through a Jungian Psychology lens. This exercise, it is worth emphasizing, does not have any proselytizing character, although it may eventually be incorporated into our own therapeutic practice, as an example or model of narrative. Thus, initially, we identified in the plot of the “Bhagavad Gita” a narrative that could be read. It involves the protagonists, namely, the warrior prince Arjuna, of the Pandavas clan, and the driver of his chariot, the god Krishna (Vishnu's avatar), in the context of the battle of Kurukshetra. Arjuna is distraught at being asked to kill relatives, masters and friends belonging to the Kurus' enemy clan. Paralyzed, he asks for the advice of Krishna, who instructs him to come out of this state, participate in the victory of his clan and advance on the spiritual path. This learning, which we call "Arjuna's Dharma", is the object of our reading, which is based on Jungian theory and its central elements (ego, self, complexes, persona, individuation process). The question we worked as hypothesis with was the following: is it possible to interpret “Arjuna's dharma” as a journey similar to that of the individuation process? The answer, developed from the crossing of fields and a careful reading of the chapters that make up the “Bhagavad Gita” (in the translation published in Brazil by ISKON), is affirmative